Niek Pas, Provo! Mediafenomeen 1965-1967 - Duivenvoorden, Eric (BMGN - Low Countries Historical Review, 2016)
Niek Pas, Provo! Mediafenomeen 1965-1967 (Amsterdam: Wereldbibliotheek, 2015, 256 pp., isbn 978 90 284 2595 8).